Optimalisasi Sosial Media Untuk Penguatan Karakter Religius Generasi Muda di Era Digital - Putri Utami Ramadhan; Rizal Nugraha Hidayat (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2024)
The increasing use of social media among the younger generation has become a major concern in the context of character development and religious values. This article aims to investigate the potential and effectiveness of utilizing social media platforms as a tool that can strengthen the religious character of the younger generation in the digital era by the Shift Pemuda Hijrah community. This research method is based on a qualitative approach, with data collection using in-depth interviews, participant observation, and social media content analysis. The results of the study indicate that social media can be optimized for strengthening religious character by the Shift Pemuda Hijrah community. Social media can be an agent for forming the religious character of the younger generation if used wisely, creatively, and responsibly. Religious character that is strengthened through digital space will provide a strong foundation for the younger generation to face global challenges, without losing the values ​​of faith and nationality.